Molecular mechanism of synergistic tyrosinase inhibition by blueberry and black chokeberry anthocyanidins: Optimal synergistic formulation for multi-berry beverage development - Du, Yuxin; Zhao, Lanqiong; Yuan, Zixuan; Zhang, Yu; Chen, Yuxin; Ding, Yang; Jiao, Xinyao; Zhao, Chong; Shimizu, Kuniyoshi; Yang, Baoru; Li, Zhongxia; Li, Bin; et al. (Elsevier, 2026)
Tyrosinase is the rate-limiting enzyme in melanogenesis and food browning, making its inhibitors crucial for health and food preservation. However, the specific mechanisms by which multi-berry formulations synergistically inhibit tyrosinase remain uncharacterized, particularly within the context of overcoming bioactivity limitations caused by standardized food ingredients. Our study revealed that blueberry-black chokeberry extracts at 1:1 ratio with superior synergistic inhibition in tyrosinase. Using affinity-ultrafiltration coupled with ultra–performance liquid chromatography–mass spectrometry (AUF–UPLC–MS), sixteen inhibitors were identified, notably delphinidin-3-O-galactoside (IC50 = 45.06 ± 1.32 μM) and cyanidin-3-O-arabinoside (IC50 = 55.54 ± 0.83 μM) displayed the highest binding affinities with synergistic inhibition at 4:1-ratio. This anthocyanin mixture exhibited reversible mixed-type inhibition, with Lineweaver-Burk analysis and multi-spectroscopic studies confirming stable complex formation. Molecular docking and dynamics simulations revealed the mixture sequence-specific inhibition mediated by enhanced hydrogen bonding that prevented drastic structural changes. The anthocyanin mixture also exhibited enhanced processing stability. These findings provided mechanistic foundations for developing multi-berry-derived anti-tyrosinase ingredients, enabling bioactivity maximization in industrial food processing.